Educação do campo na Educação Superior: as repercussões do PRONERA na atuação social, profissional e política de egressos dos cursos ofertados na UFPB (CAMPUS I) - Ferreira, Suellen Cristina Rodrigues (2018)
This research deals with Education in countryside in the area of Higher Education directed to the subjects who live/work in the countryside through the experiences of Programa Nacional de Educação na Reforma Agrária - PRONERA (the National Program of Education in Agrarian Reform) which is the analysis object of this work. Therefore, the main object of this research is to analyze the repercussions of PRONERA on the social, professional and political performance of those who graduated (got degree) both offered at the courses of Pedagogy and History at the Federal University of Paraíba – UFPB (campus I). The research seeks to meet the following specific objectives as: analyzing the statistical data published in the II PNERA report, regarding the provision of higher education to the settlers of the Agrarian Reform in Paraíba; and identifying the repercussions of PRONERA on the social, professional and political performance of people who got graduated in the Higher Education courses offered at UFPB. This study is characterized as a qualitative research and the repercussions which were analyzed along the text are based on the Dialectical Historic Materialism perspective. Therefore, this work was also based in complementary methodological procedures such as bibliographical and documentary research and interview of those who graduated at the Program. Our focus on this research of these courses allowed us to discuss the history, concept and practices of Education in the countryside area, and allowed us to discover the reach of PRONERA in the life of countryside people. Therefore, we understand PRONERA Program as an educational proposal based on a peasant perspective, and this program had positive repercussions on the countryside people lives, increasing the level of schooling, promoting the continuity of studies, making possible the professional insertion, permanence in the countryside area and the valorization of family agriculture, fomenting discussions and practices of Education in the countryside area in the schools of the settlements, strengthening the peasant identity and providing the political engagement and the strengthening of the political action in social movements.